2020
DOI: 10.1002/acr.23933
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Opioid and Benzodiazepine Prescriptions for Osteoarthritis

Abstract: Objective. Opioids and benzodiazepines are commonly used for management of osteoarthritis, despite evidencebased recommendations to the contrary. This study aimed to quantify the prevalence of opioid and benzodiazepine prescribing for osteoarthritis. Additionally, we aimed to characterize risk factors for prescription drug misuse, abuse, and diversion among this population.Methods. We conducted a descriptive analysis of adult outpatient encounters with a primary diagnosis of osteoarthritis during a 1-year peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
1
10
1
Order By: Relevance
“…In contrast, a recent publication from Belgium [22] reported that NSAIDs were prescribed to 29.4% of knee OA patients in 2015, a relatively similar rate to our observation in Israel. We found that 22.9% of OA patients used opioids, similar to the rates observed in Sweden (23.7%) [23] and the US (27%) [31], but higher than the 10% reported in Belgium [22] and Japan [18]. Paracetamol was used by approximately 20% of the OA patients in our study, a similar rate to Japan [18] and Belgium [22], but much higher than in Korea [21].…”
Section: Analgesic Usesupporting
confidence: 84%
“…In contrast, a recent publication from Belgium [22] reported that NSAIDs were prescribed to 29.4% of knee OA patients in 2015, a relatively similar rate to our observation in Israel. We found that 22.9% of OA patients used opioids, similar to the rates observed in Sweden (23.7%) [23] and the US (27%) [31], but higher than the 10% reported in Belgium [22] and Japan [18]. Paracetamol was used by approximately 20% of the OA patients in our study, a similar rate to Japan [18] and Belgium [22], but much higher than in Korea [21].…”
Section: Analgesic Usesupporting
confidence: 84%
“…Delayed virus clearance for SARS 74 and MERS 73 but reduced mortality with SARS. 77 No association with virus clearance and duration of symptoms in COVID-19 80 No evidence for discontinuation for systemic treatment -Balance cost/benefit for patients with weak symptoms Opioids Abuse and misuse, 93 constipation, nausea/ vomiting, 94 respiratory depression. 85 Increased risk for general AEs in OA patients.…”
Section: Oa Drugs and Viral Infections: What Do We Know?mentioning
confidence: 99%
“…91 Notably, considering the different administration routes, no differences in the overall adverse event profile emerged between transdermal opiates and oral treatments. 92 Nevertheless, the risk for adverse outcomes due to opioid abuse remains, since more than 20% of OA patients receiving prescriptions have a risk factor for misuse, 93 and associated adverse events (constipation, nausea/vomiting). 94 Being aware of the several molecules used in OA management, we will below report available information about two widely prescribed weak opioids, with and without immunosuppressive activity, due to their possible reduced interaction with respiratory tract infections and their preferential use in place of paracetamol or NSAIDs.…”
Section: Reviewmentioning
confidence: 99%
“…PRISM is a novel resilience intervention for AYAs with cancer that has shown higher patient-reported resilience, quality of life, hope, and benefit finding and lower distress, thus resulting in parents of AYAs wanting similar intervention for themselves. 3,4 Hence, PRISM-P was adapted. To minimize variance, the same psychologist delivered this phase 2 trial.…”
Section: Distress and Resilience Among Ayas And Their Mothersmentioning
confidence: 99%
“…First, concurrent opioids/benzodiazepine-S use remains higher in the cancer population than other populations. 4,5 Next, it is possible to transition some patients receiving these combinations to other nonsedating agents without worsening their symptoms.…”
mentioning
confidence: 99%